2016
DOI: 10.3998/jmmh.10381607.0010.201
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Religious Coping and Wellbeing in Acculturating Muslims

Abstract: Situated within an international context of Islamophobia, this study examined acculturative stress, religious coping, and their interaction as predictors of subjective wellbeing in 167 New Zealand Muslims. A Muslim Religious Coping (MRC) scale was adapted for the purposes of this study, measuring religious coping across three domains of Cognitive, Behavioral, and Social MRC. Consistent with hypotheses: 1) acculturative stress predicted a lower level of Life Satisfaction and more psychological symptoms, and 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 60 publications
3
44
0
Order By: Relevance
“…Many Latin American cultures stress the prominence of family (Bacallao & Smokowski, 2007), which helps to reduce stress and promote feelings of connectedness (Falicov, 2013). Middle Eastern cultures tend to emphasize religion, and research indicates that Muslim immigrants use their faith to cope with discrimination and promote well-being (Adam & Ward, 2016; Hakim et al, 2017). These are just some culturally specific values immigrant populations possess, and the field should identify others, as well as how such values facilitate positive adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Many Latin American cultures stress the prominence of family (Bacallao & Smokowski, 2007), which helps to reduce stress and promote feelings of connectedness (Falicov, 2013). Middle Eastern cultures tend to emphasize religion, and research indicates that Muslim immigrants use their faith to cope with discrimination and promote well-being (Adam & Ward, 2016; Hakim et al, 2017). These are just some culturally specific values immigrant populations possess, and the field should identify others, as well as how such values facilitate positive adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that disempowered and deprived groups, including women and ethnic minorities, resort to the use of religious coping and found great efficacy in it [43]. In addition, religious coping has been shown to be extensively used when situations are deemed uncontrollable [41, 47], thus providing an outlet for those at a social disadvantage and with limited access to external resources [48]. Based on these findings, it is apparent that religious coping serves as a resilience mechanism as it enhances a more stable and positive measures of wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from research among recent Muslim immigrants in Chicago supported religious coping framework, which argued that religion mediated stressful experiences in the new social environment by providing meaning and hope in immigrants' lives (Pargament, 1997). That linked to cross-national research on Muslim immigrants and religious coping in other Western countries (Adam and Ward, 2016). At the same time, Islamic religious identity did not help first generation Central Asian immigrants to bridge their way to mainstream American society.…”
Section: Dicsussionmentioning
confidence: 97%
“…Research among Latino immigrants showed that religious coping played an important role in the experiences of movers, and mitigated acculturation stress in the new social setting (Da Silva et al, 2017;Sanchez et al, 2012). Although religious coping framework was well-established for Christian populations, research on Muslim religious coping among immigrants in Western countries pointed at conflicting evidence on the role of religion as a buffer of stress (Adam, 2016;Ghaffari and Ciftci, 2010). Rippy and Newman (2006) argued that Islamic religious affiliation increased stress, anxiety and depression through immigrants' experiences of discrimination (and see Ghaffari and Ciftsi, 2010).…”
Section: Introductionmentioning
confidence: 99%